Association Between Obsessive Compulsive Disorder And Tumor Necrosis Factor-Α Gene –308 (G>A) And –850 (C>T) Polymorphisms In Turkish Children - Lüleyap H.U. (Balkan Journal of Medical Genetics, 2012)
Obsessive compulsive disorder (OCD) is a neurobiological disease characterized with obsessions and compulsions. Obsessive compulsive disorder occurs with an autoimmune mechanism after Group A β hemolytic streptococcus (GABHS) infection. Tumor necrosis factor (TNF) is an important cytokine, as well as having an important role in the apoptosis mechanism of autoimmune diseases. It is expressed by the TNF-α gene. The aim of this study was to examine the relationship between the TNF-α gene promoter region -308 (G>A) and -850 (C>T) polymorphisms and OCD. In this study, ages of the OCD patients and the control group ranged between 4 and 12 years. We studied two patient groups, one included childhood onset OCD patients (n = 49) and the control group was composed of healthy children (n = 58). Patients were diagnosed according to the Diagnostic and Statistical Manual of Mental Disorder (DSM-IV) criteria and with Kiddie Schedule for Affective Disorders and Schizophrenia-Present and Lifetime (KSAD-S-PL) version. For identifying the polyorphisms, polymerase chain reaction (PCR), restriction fragment length polymorphism (RFLP) and polyacrylamide gel electrophoresis (PAGE) methods were used.